2005
DOI: 10.1007/s00122-004-1902-7
|View full text |Cite
|
Sign up to set email alerts
|

A high-density genetic map of hexaploid wheat (Triticum aestivum L.) from the cross Chinese Spring × SQ1 and its use to compare QTLs for grain yield across a range of environments

Abstract: A population of 96 doubled haploid lines (DHLs) was prepared from F1 plants of the hexaploid wheat cross Chinese Spring x SQ1 (a high abscisic acid-expressing breeding line) and was mapped with 567 RFLP, AFLP, SSR, morphological and biochemical markers covering all 21 chromosomes, with a total map length of 3,522 cM. Although the map lengths for each genome were very similar, the D genome had only half the markers of the other two genomes. The map was used to identify quantitative trait loci (QTLs) for yield a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
290
7
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(334 citation statements)
references
References 55 publications
33
290
7
4
Order By: Relevance
“…Linkage analysis using an F 2 Chinese Spring 3 Renan population with 102 selected markers resulted in a genetic map of 179.1 cM in length (Figure 1), which is in the range of the genetic map length reported for chromosome 3B in the literature (Quarrie et al 2005;Suenaga et al 2005;Akbari et al 2006). This represented an average of 1 marker for every 1.75 cM.…”
Section: Resultsmentioning
confidence: 68%
“…Linkage analysis using an F 2 Chinese Spring 3 Renan population with 102 selected markers resulted in a genetic map of 179.1 cM in length (Figure 1), which is in the range of the genetic map length reported for chromosome 3B in the literature (Quarrie et al 2005;Suenaga et al 2005;Akbari et al 2006). This represented an average of 1 marker for every 1.75 cM.…”
Section: Resultsmentioning
confidence: 68%
“…Comparative analysis with the known major QTL for yield in wheat: A survey of the literature reporting QTL for GY and related agronomic traits in both tetraploid and hexaploid wheat (Li et al 2002;Peng et al 2003;Elouafi and Nachit 2004;Huang et al 2004Huang et al , 2006McCartney et al 2005;Quarrie et al 2005Quarrie et al , 2007Marza et al 2006;Narasimhamoorthy et al 2006;Kuchel et al 2007;Kumar et al 2007;Ma et al 2007) revealed rather different scenarios for the two major GY QTL identified in our study. Our comparative analysis was carried out by relating the (LOD À 1) supporting interval of the QTL to the Ta-SSR-2004 consensus map (Somers et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This notwithstanding, the knowledge gained so far for grain yield determinants is still incomplete. In fact, QTL for yield and yield-related traits most frequently account for between $2 and 10% of the total phenotypic variation; major QTL with R 2 values $15% have seldom been described, especially when evaluating segregating materials obtained from elite accessions (Quarrie et al 2005;Dilbirligi et al 2006). The identification of QTL with major and environmentally stable additive effects is even more desirable when targeting drought-prone environments where the spatial and temporal phenotypic variation (including G 3 E effects) is usually larger than that observed in favorable environments (Lanceras et al 2004), a condition that lowers the heritability of target traits.…”
mentioning
confidence: 99%
“…Moreover, both processes-N uptake and N utilization-appear to be governed by different genetic factors (Hirel et al 2001;Gallais and Hirel 2004;Good et al 2004). For instance, results of extensive molecular studies on wheat and maize Gallais 2000, 2001;Quarrie et al 2005;Habash et al 2007;Laperche et al 2007) revealed that different sets of genes (QTL regions) controlled various components of the two major measures of N efficiency, and that expression of the genes (loci) was considerably dependent upon soil N status. Hence, the appearance of the above-mentioned negative relationship between NUpE and NUtE in the examined hybrids and their parents may be a genetic quandary.…”
Section: Combining Ability Effectsmentioning
confidence: 99%
“…However, the genetic control of whole-season N efficiency has rarely been examined in wheat. Recent extensive molecular studies (Charmet et al 2005;Quarrie et al 2005;Habash et al 2007;Laperche et al 2008;Fontaine et al 2009) identified numerous genome regions (QTLs) responsible for grain yield structure and nitrogen yield under N limitations, grain protein content and N metabolism in the uppermost foliage as well as for the activity of glutamine synthetase and glutamate dehydrogenase, the key enzymes involved in N assimilation. In earlier investigations (Le Gouis et al 2002), both additive and non-additive genetic effects were crucial for agronomic NUE components in F 1 hybrids between modern French cultivars.…”
Section: Introductionmentioning
confidence: 99%